Book Review: Rawai al Bayan Fi Tafsir Ayat al Ahkam min al Qur’an (Haste of Tarjih Muhammad Ali al Shabuni) - Much. Mu'alim; Idri Idri; Afifuddin Dimyathi (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2021)
Muhammad Ali al Shabuni had produced many papers in these two scientific fields, including Rawai al Bayan, a book that combines between jurisprudence and interpretation. Not all results of Al Shabuni’s tarjih in the book of Rawai al Bayan can be used as hujjah (evidence and legal handle), because there are still some Tarjih processes that did not correspond to the stages must be passed. The majority of Tarjih results that he had attempted can be used as hujjah because it has fulfilled the stages of Tarjih implementation in question. Regardless of the problem, it is worth acknowledging that the book of Rawai al Bayan by Al Shabuni has enlightened in the interpretation of Ahkam verses, because it is more structured and objective to do Tarjih, when compared to many books of interpretation of Ahkam verses before. Keywords: Rawai al Bayan; Muhammad Ali al Shabuni; book review